Modification Mechanism of Asphalt Modified with Rock Asphalt and Styrene-Butadiene Rubber (SBR) - Xiangming Deng; Hui Huang; Bin Wang; Jie Chen (Advances in Civil Engineering)
High-performance asphalt binder plays an important role in the durable asphalt pavement. Asphalt modified by rock asphalt (RA) is one of the high-performance modified asphalt materials. It was used in road engineering as a relatively environmentally friendly material, because rock asphalt takes some advantages of large reserves, easy treatment, and efficient modification. Moreover, the main component of rock asphalt is bitumen, which enables it to substitute part of the binder used in asphalt mixtures. On the other hand, the negative low-temperature performance of RA modified asphalt impeded its application in cold regions. The object of this paper is to improve the low-temperature performance of RA modified asphalt by compound modified with styrene-butadiene rubber (SBR). The 70-penetration grade binder and the RA modified asphalt with 15% RA by weight were applied as the base binder. Five types of RA-SBR modified asphalt were prepared, and the content of SBR was 2%, 4%, 5%, 6% and 8% by weight of BRA modified binder. The Fourier transform infrared spectroscopy (FTIR) tests were utilized to illustrate the reasons for the poor low-temperature performance of BRA modified asphalt and reveal the compound modification mechanism of BRA-SBR modified asphalt. The Brookfield viscosity test, dynamic shear rheometer test, and bending beam rheometer test were adopted to reveal the variation patterns of rheological behavior and low-temperature performance with mass contents of SBR. The test results indicated that the worse of low-temperature performance was caused by the increase of asphaltene content and the stress concentration due to ash in RA modified asphalt. And the compound modification is a physical process. The addition of SBR has improved the low-temperature performance of RA modified asphalt dramatically. And based on the rheological behaviors and low-temperature performance of RA-SBR compound modified asphalt, the optimum content of SBR was determined, which is about 4%∼5%.